2022
DOI: 10.48550/arxiv.2203.01764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Random Quantum Neural Networks (RQNN) for Noisy Image Recognition

Abstract: Classical Random Neural Networks (RNNs) have demonstrated effective applications in decision making, signal processing, and image recognition tasks. However, their implementation has been limited to deterministic digital systems that output probability distributions in lieu of stochastic behaviors of random spiking signals. We introduce the novel class of supervised Random Quantum Neural Networks (RQNNs) with a robust training strategy to better exploit the random nature of the spiking RNN. The proposed RQNN e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Few examples include image classification (MNIST dataset) [ 44 , 84 ], computational biology [ 85 ], and high-energy physics [ 86 ]. The QNN framework has found applications in image classification [ 87 ], cyber-security [ 88 ], medical [ 89 ], and high-energy physics problems [ 90 , 91 ]. has been used for image classification [ 66 ], remote sensing [ 92 ], and medical applications [ 93 ].…”
Section: Quantum Neural Network Technologies and Methodologiesmentioning
confidence: 99%
“…Few examples include image classification (MNIST dataset) [ 44 , 84 ], computational biology [ 85 ], and high-energy physics [ 86 ]. The QNN framework has found applications in image classification [ 87 ], cyber-security [ 88 ], medical [ 89 ], and high-energy physics problems [ 90 , 91 ]. has been used for image classification [ 66 ], remote sensing [ 92 ], and medical applications [ 93 ].…”
Section: Quantum Neural Network Technologies and Methodologiesmentioning
confidence: 99%
“…We compare the model proposed in this paper with other recent quantum neural network classification algorithms in noisy environments. Here, we classify the test subset of the FashionMNIST dataset using SQNN [47] and RQNN [48]. This experiment still selected 400 test samples.…”
Section: Fashionmnist Accuracy and Anti-noise Testmentioning
confidence: 99%
“…Jang et al showed in their work that DNNs are susceptible to spatially uncorrelated white noise, and by introducing a noise learning procedure, it is possible to provide a better qualitative match to human performance [37]. In [38], a controlled random quantum neural network was proposed that used hybrid classical quantum algorithms with superposition and amplitude state coding functions, which improved not only the classification accuracy on MNIST, FashionMNIST, and KMNIST data, but also stability under conditions of increased noise. Also, a complex valued multilayer neural network with multivalued neurons (MLMVN) was adapted and successfully applied to filter impulse noise [39].…”
Section: Research Motivationmentioning
confidence: 99%